1983
DOI: 10.1080/00268978300100281
|View full text |Cite
|
Sign up to set email alerts
|

Conformational entropy of a bilayer membrane derived from a molecular dynamics simulation

Abstract: The conformational entropy of the disordered hydrocarbon chains in a bilayer membrane is calculated from a molecular dynamics simulation. We find that one chain in the mean field of the others is very well described by a trans-gauehe model with adjacent gauches of opposite sign forbidden. The effective gauche energy depends, however, on the density of chains and may for realistic densities be between 4"5 and 5-7 kJ mo1-1. This gives a conformational entropy of the disordered phase close to the gel-liquid cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…It has been shown previously [I] that the experimental entropy for the K + KM phase transition in lead(I1) decanoate is in good agreement with that predicted from a molecular dynamics simulation of chain disordering [39].…”
Section: Thermodynamics Of the Phase Transitionssupporting
confidence: 78%
See 1 more Smart Citation
“…It has been shown previously [I] that the experimental entropy for the K + KM phase transition in lead(I1) decanoate is in good agreement with that predicted from a molecular dynamics simulation of chain disordering [39].…”
Section: Thermodynamics Of the Phase Transitionssupporting
confidence: 78%
“…The same criticism does not apply to molecular dynamics calculations [39], where one is modelling the total change in conformation and packing of the chains. However, this can be circumvented by obtaining entropy changes from a free energy decomposition [41].…”
mentioning
confidence: 95%
“…The conventional model of a biological membrane is a lipid bilayer in which are embedded many proteins and sterols (Cevc and Marsh, 1987) all held together by noncovalent interactions. Interest in modeling bilayer membranes using molecular dynamics has increased dramatically (Bassolino-Klimas et al, 1993; Biswas and Shurmann, 1991;Charifson et al, 1990;Damodaran et al, 1992;Merz, 1993, 1994;Edholm et al, 1983;Edholm and Johansson, 1987;Edholm and Nyberg, 1992; Egberts and Berendsen, 1988;Essex, 1992;Fukada et al, 1993;Heller et al, 1993; Khalatur and Pavlov, 1987;Marrmnk et al, 1993; van der Ploeg and Berendsen, 1982Stouch et al, 1991Stouch et al, , 1994Stouch, 1993;Venable et al, 1993;Xiang, 1993). Of these only a few have been attempts with phospholipid molecules and explicit solvent (Damodaran et al, 1992;Merz, 1993,1994;Essex, 1992;Heller et al, 1993;Stouch, 1993;and Venable et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…A considerable amount of experimental data is available on this system, which exhibits two mesophases between the solid and isotropic liquid. Further, the chain length is of interest because a number of good theoretical calculations have been performed on chain disordering in 10 carbon atom systems (24)(25)(26)(27). From X-ray powder diffraction studies, a layered lamellar structure has been confirmed for the solid phase, with planes oflead(II) ions separated by the carboxylate chains (20,28).…”
Section: General Phase Behaviourmentioning
confidence: 95%